2012
DOI: 10.1158/1535-7163.mct-11-0575
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibition of Angiogenesis by the IGF-1 Receptor-Targeting Antibody SCH717454 Is Reversed by IGF-2

Abstract: Previously, we reported that a predominant action of an IGF-1R-targeted antibody was through inhibiting tumor-derived VEGF, and indirectly, angiogenesis. Here we examined the direct anti-angiogenic activity of the IGF-1R-targeted antibody SCH717454 that inhibits ligand-receptor binding, and the mechanism by which tumors circumvent its anti-angiogenic activity. Inhibition of ligand stimulated activation of IGF-1R, insulin receptor (IN-R) or downstream signaling (phosphorylation of Akt [Ser473]) was determined b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 45 publications
6
61
0
Order By: Relevance
“…Our findings are supported by a recent study that IGF-1R-targeted antibody SCH717454 completely blocked VEGF-A-induced HUVEC proliferation, migration, tube formation, and in vivo vessel formation (39). Interestingly, the blocking effect of the antibody on VEGF-A signaling could be reversed by exogenous IGF-2 or insulin, but not by exogenous IGF-1, suggesting that the antibody might directly neutralize IGF-1 ligand released into the extracellular space or cause degradation of transmembrane IGF-1R (39). Nevertheless, the study did not address how the IGF-1R antibody affects VEGF-A signaling, directly or indirectly.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are supported by a recent study that IGF-1R-targeted antibody SCH717454 completely blocked VEGF-A-induced HUVEC proliferation, migration, tube formation, and in vivo vessel formation (39). Interestingly, the blocking effect of the antibody on VEGF-A signaling could be reversed by exogenous IGF-2 or insulin, but not by exogenous IGF-1, suggesting that the antibody might directly neutralize IGF-1 ligand released into the extracellular space or cause degradation of transmembrane IGF-1R (39). Nevertheless, the study did not address how the IGF-1R antibody affects VEGF-A signaling, directly or indirectly.…”
Section: Discussionsupporting
confidence: 90%
“…Also, our experiment showed that IGF-2 was continually released into the culture media of cultured hAM over the 48 h time period. Bid et al suggested role for IGF-2 in angiogenesis on HUVECs culture model [30]. We propose that the observed migratory effect on HUVEC may be due to the IGF-2 presence in the 24 h hAM culture medium or appearance of other released, however, not tested factors.…”
Section: Discussionmentioning
confidence: 65%
“…IGF-1 has been shown to stimulate hypoxia-inducible factor-1a activity and VEGF expression in several cancer models (25)(26)(27)(28). Blockade of the IGF-1 pathway inhibited angiogenesis and tumor growth in experimental animals (29)(30)(31)(32). It is plausible that our HCC patients who had high serum IGF-1 levels might have tumors with higher angiogenic activity, which renders them more likely to benefit from antiangiogenic therapy.…”
Section: Discussionmentioning
confidence: 95%